Pengaruh Gaya Kepemimpinan Dan Kompensansi Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Budiman Swalayan - Arya Garin Nugraha; Bintang Satria Bahri; Farhan Habiba; Fikru Irwanda; Chintya Ones Charli (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to analyze the influence of leadership style and compensation on employee performance with job satisfaction as an intervening variable at Budiman Swalayan with a sample of 100 respondents. This type of research is explanatory research. The method used is data collection using a questionnaire. smart PLS analysis method